Cultural adaptation of the Mental Illness: Clinicians' Attitudes Scale (MICA-4) for Brazilian context - Raquel Helena Hernandez Fernandes; Carla Aparecida Arena Ventura; Simone de Godoy Costa (Universidade Estadual de Maringá, 2024)
This study aims to describe the cultural adaptation of the Mental Illness: Clinicians' Attitudes Scale (MICA-4) for Brazilian context through the description of the translation and back-translation process, face and content validity assessment and reliability assessment. The method for cultural adaptation occurred through translation of the original instrument, evaluation by the Committee of Judges, back-translation and pre-test. The results of the pre-test demonstrated that the MICA-4 is understandable and applicable, in addition to having good internal consistency, with a Cronbach's alpha of 0.75. The Brazilian version of MICA-4 has been demonstrated to be easily applicable, with language suitable for the Brazilian context, presented in an appropriate format, and displaying sufficient understanding and consistency with the original version. This culturally adapted version of MICA-4 for the Brazilian context is suitable for conducting a study to assess its psychometric properties.